Molecular Docking and Pharmacokinetic Prediction Studies of Novel Coumarin Derivatives as Arylamine N- acetyltransferase 2 Inhibitors - George, Shiny; Sujith, P. K.; Chandran, Meena; Santhalingam, Kumaran (Current Aspects in Pharmaceutical Research and Development Vol. 2, 2021)
Arylamine N-acetyltransferases are xenobiotic-metabolizing enzymes responsible for detoxification of many drugs and carcinogens. It catalyzes the N- or O-acetylation of various arylamine and heterocyclic amine substrates and is able to bioactivate several known carcinogens. The levels of NATs in the body have important consequences with regard to an individual's susceptibility to certain drug-induced toxicities and cancers. Objective of present study is to analyse the affinity of computationally designed coumarin derivatives on NAT2 with AutoDock 4.0.1 software and to investigate the interactions between the target compounds and the amino acid residues of the enzyme. Molecular properties of designed compounds were studied by using Molinspiration. All compounds obeyed lipinski rule of five which suggest that these compound have excellent drug likeness properties and are preferable as an orally acting drug. In present study, pharmacokinetic prediction on coumarin derivatives were done using pkCSM software. ADMET properties prediction results shown that all designed compounds possess well metabolic characteristics without obvious toxicities. Among the designed compounds 3, 6- dibutyl-7-hydroxy-4-oxo-2-chlrobenzyl -4H chromene -8- carbaldehyde (compound 5) shows more binding energy value (-9.08). These values suggested that the designed coumarin derivatives are excellent inhibitors of NAT2.